SARS-CoV-2 tests in occupational settings: what you look for is what you get - Ferrari, Luca; Nigro, Simona; Bordini, Lorenzo; Carugno, Michele; Bollati, Valentina (La Medicina del Lavoro, 2021)
During the last month of 2019, a new Coronavirus from China started to spread all around the world causing a pandemic emergency still ongoing. The outbreak made imperative the need for diagnostic and screening tests that could identify the current and past infection state of an individual. Occupational medicine is facing a very demanding challenge, as the pandemic set off the need to re-evaluate many aspects of workplace safety. A fundamental role has been played by tests used to diagnose COVID-19 and to isolate infected asymptomatic subjects, with a view to the viral evolution and the emerging variants. However, the need for the urgent set-up of new methods for assessing both new and past infections has resulted in a large number of methods, not always comparable with each other, in terms of laboratory techniques, viral antigens used for detection, and class of antibodies detected. These factors make it difficult to understand the serological test results and their possible application. In this paper, we reviewed the types of assays currently available, to address some key aspects that characterize each technique, and might have an impact on results interpretation.